Orexin Signaling: A Complex, Multifaceted Process - Dale, Natasha C.; Hoyer, Daniel; Jacobson, Laura H.; Pfleger, Kevin D. G.; Johnstone, Elizabeth K. M. (Frontiers in Cellular Neuroscience, 2022)
The orexin system comprises two G protein-coupled receptors, orexin 1 receptor (OX1R) and orexin 2 receptor (OX2R), along with two endogenous agonists cleaved from a common precursor (prepro-orexin), orexin-A (OX-A) and orexin-B (OX-B). When discussing the system’s G protein coupling capabilities, it is commonly stated that both receptors couple to Gq cascades while OX2R also couples to Gi cascades. However, a complex milieu of signalling behaviour has been reported that expands and complicates this narrative. In particular, it becomes obvious that orexin receptor coupling is very diverse and can be tissue-, cell- and context-dependent. Here, the early signal transduction interactions of the orexin receptors will be discussed in depth, with particular emphasis on the direct G protein interactions of each receptor. In doing so, it is evident that ligands, additional receptor-protein interactions and cellular environment all play important roles in the G protein coupling profiles of the orexin receptors. This has potential implications for our understanding of the orexin system’s function in vivo in both central and peripheral environments, as well as the development of novel agonists, antagonists and possibly allosteric modulators targeting the orexin system.